Bihar Third Five Year Plan Progress Report for the Period March, 1965 - Planning Commission (Planning Commission, 1965)
Agricultural Programme, Co-operation, Community Development and Gram Panchayat, Irrigation and Flood Control, Power, Industries and Mining, Transport and Communications, Social Services.
Bihar